Pyridazinone substituted benzenesulfonamides as potent carbonic anhydrase inhibitors. Issue 4 (15th February 2016) - Yaseen, Raed; Ekinci, Deniz; Senturk, Murat; Hameed, Alhamzah Dh.; Ovais, Syed; Rathore, Pooja; Samim, Mohammed; Javed, Kalim; Supuran, Claudiu T.
Graphical abstract: Abstract: A series of sulfonamide derivatives (2a –l ) incorporating substituted pyridazinone moieties were investigated for the inhibition of two human cytosolic carbonic anhydrase isoforms, hCA I and hCA II. All these compounds, together with the clinically used sulfonamide acetazolamide were investigated as inhibitors of the physiologically relevant isozymes I and II. These sulfonamides showed very strong inhibition against all these isoforms with K I 's in the range of 0.98–8.5 nM which makes such molecules possible to be used as leads for discovery of novel effective CA inhibitors targeting other isoforms with medicinal chemistry applications.